Benefits of delapril in hypertensive patients along the cardiovascular continuum. (March 2013) - González-Juanatey, José Ramón; Cordero, Alberto
Angiotensin-converting enzyme inhibitors (ACEIs) are the first-line therapy for the treatment of hypertension. However, not all ACEIs are equal. Delapril is a nonsulfhydryl ACEI with unique properties. Delapril has a high lipophilicity and weak bradykinin potentiating action. As a result, delapril has a more potent inhibition capacity of vascular wall angiotensin-converting enzyme activity and a lower incidence of cough than enalapril or captopril. With regard to efficacy, delapril has a long-lasting antihypertensive effect with a trough/peak ratio that is in the upper range of different ACEIs and a positively high smoothness index. Thus, delapril effectively and smoothly reduces blood pressure over 24 h. Moreover, the benefits of delapril are not limited to hypertensive patients, but also in those with microalbuminuria, left ventricular hypertrophy, myocardial infarction or heart failure; delapril appears to be effective and well tolerated.